Application of Cooperative Learning Model Assisted Individualization Teams To Improve Student Results In Human Digestive System Material In 11th Grade Science Public High School 14 Tebo Jambi - Arjoni, Muhammad; Seri, Herman; Hidayat, Saleh (UIN Fatmawati Sukarno Bengkulu, 2021)
The problem in this study is whether the cooperative learning model type Teams Assisted Individualization(TAI) can improve student learning outcomes in Biology subjects in 11th Grade Science Public High School14 Tebo Jambi? This study aims to improve student learning outcomes from the domains of studentknowledge, attitudes and skills through the Application of Teams Assisted Individualization (TAI)Cooperative Learning Model in 11th Grade Science Public High School 14 Tebo Jambi. The research wasconducted at Public High School 14 Tebo Jambi, involving 30 students consisting of 15 boys and 15 girlswho were registered in the 2019/2020 school year. This study used a Classroom Action Research (CAR)design with a Kart Lewin research design consisting of two cycles. Each cycle held two meetings in theclassroom and each cycle consists of four stages: planning, implementation, observation, and reflection. Theresults showed that the learning outcomes in the realm of knowledge obtained a class average score in thefirst cycle of 63.08 and in the second cycle the class average score was 78.93 with a classical percentage of78.57%. In the realm of attitude, the class average score for the first cycle was 66.31. Cycle II, with a classaverage of 74.86. And in the realm of skills, the class average score in the first cycle is 51.73. While in cycleII the class average value was 77.88. So it can be concluded that there is an increase in student learningoutcomes in the domains of knowledge, attitudes and skills after the application of the Teams AssistedIndividualization (TAI) cooperative learning model in Biology subjects in 11th Grade Science at Public HighSchool 14 Tebo Jambi